Enhancing Grit and Critical Thinking in Rural Primary Students: Impact of a Targeted Educational Intervention - Carla Gallardo-Estrada; Miguel Nussbaum; Mauricio Pinto; Danilo Alvares; Carlos Alario-Hoyos (MDPI AG, 2024)
This study examined the impact of a targeted educational intervention on enhancing grit and critical thinking skills among 10-year-old primary school students in rural Chile. The intervention, involving 153 students from six public schools, used a language classroom model with structured reading activities. Grit and critical thinking were measured pre- and post-intervention. Results showed improvements in the intervention group. The intervention's effectiveness was consistent across genders. The findings suggest that structured, student-centered educational strategies can enhance grit and critical thinking in primary students. Further research is needed to generalize the results to different settings and age groups.